The effect of hatching altitudes and broiler strains on the prevalence of ascites syndrome - Siamak Pourghasemi khiavi; Habib Aghdam Shahryar; Ramin Salamatdoust Nobar; Abolfazl Ghorbani (Journal of Applied Poultry Research)
Summary: Ascites in broilers is a metabolic disorder causing substantial economic losses in the poultry industry. This study aimed to investigate the effects of broiler strains (Ross 308 and Cobb) and hatching altitude (Rasht 0 m and Tabriz 1400 m) effects on the incidence of ascites syndrome and related traits. Two hundred forty hatching eggs of the same weight (64±1 gram) were used. The eggs hatched in both locations simultaneously. The studied parameters were incidence of ascites syndrome at 14, 21, and 42 days, lung and heart volume at 14 and 42 days, carcass performance, antioxidant status, hematological measurements, thyroid hormone levels, nitric oxide, lipid profile, uric acid, and liver enzyme level. Results showed that the strain on SOD, T3, and cholesterol, hatching altitude on lung and heart volume at 42 days, and T3, and the interaction of strain at hatching altitude on lung and heart volume at 42 days, spleen percentage, nitric oxide level, and RV-to-TV ratio were significant effect (p < 0.05). The incidence of ascites and heart volume increases with age, but lung volume decreases. Even though there is no significant difference between the two strains and the hatching altitude in most of the traits, the comparison of the numerical values of the parameters indicates that the high-altitude hatching and the Cobb strain have higher values. These data suggest that selected broiler strains and hatching environments could have a higher sensitivity to alterations in pulmonary rheological parameters at an early age, triggering the ascites syndrome.